2022
DOI: 10.3390/en15134787
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an Exhaust Thermoelectric Generator Incorporating Thermal Control Applied to a Heavy Duty Vehicle

Abstract: The road transport industry faces the need to develop its fleet for lower energy consumption, pollutants and CO2 emissions. Waste heat recovery systems with Thermoelectric Generators (TEGs) can directly convert the exhaust heat into electric energy, aiding the electrical needs of the vehicle, thus reducing its dependency on fuel energy. The present work assesses the optimisation and evaluation of a temperature-controlled thermoelectric generator (TCTG) concept to be used in a commercial heavy-duty vehicle (HDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…One promising approach involves enhancing the efficiency of conventional power conversion mechanisms through the implementation of waste heat recovery systems. This strategy not only addresses fossil fuel consumption but also mitigates its detrimental impact on climate change { [13] [14][15] }. Although waste heat recovery systems offer one solution, there are many other approaches too to reducing the fossil fuel consumption use and mitigating the greenhouse effect.…”
Section: Figure 1: Emission Gas Factormentioning
confidence: 99%
“…One promising approach involves enhancing the efficiency of conventional power conversion mechanisms through the implementation of waste heat recovery systems. This strategy not only addresses fossil fuel consumption but also mitigates its detrimental impact on climate change { [13] [14][15] }. Although waste heat recovery systems offer one solution, there are many other approaches too to reducing the fossil fuel consumption use and mitigating the greenhouse effect.…”
Section: Figure 1: Emission Gas Factormentioning
confidence: 99%
“…Therefore, researchers worldwide are searching for different methods to reduce or eliminate fossil fuel usage. Fossil fuels usage, and consequently its contribution to climate change, can be effectively reduced through the implementation of three distinct strategies: (a) enhancing the efficiency of conventional power conversion devices/systems through waste heat recovery [4][5][6]; (b) developing efficient energy conversion devices that are friendly to the environment, such as fuel cells [7][8][9]; and finally, (c) a shift toward renewable energies that comes from nature and have minimal negative effects on the environment [10][11][12]. In general, using renewable energy is the most attractive method as it could significantly decrease the usage of or even eliminate the reliance on fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that this kind of channel could make the boundary layer around the edges thinner, enhancing the amount of flow in the turbulent regime present in the fluid. Sousa et al [19] assessed the optimization and evaluation of a temperaturecontrolled thermoelectric generator to be used in a commercial 16 L heavy-duty vehicle. The system consisted of a heat exchanger with wavy fins embedded in an aluminum matrix along with heat pipes machined directly into the matrix that granted thermal control based on dissipating the local excess heat by phase change.…”
Section: Introductionmentioning
confidence: 99%